2013
DOI: 10.1002/nbm.3044
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR detects different metabolic profiles in glioblastoma stem‐like cells

Abstract: The metabolic profiles of glioblastoma stem-like cells (GSCs) growing in neurospheres were examined by (1)H NMR spectroscopy. Spectra of two GSC lines, labelled 1 and 83, from tumours close to the subventricular zone of the temporal lobe were studied in detail and compared with those of neural stem/progenitor cells from the adult olfactory bulb (OB-NPCs) and of the T98G glioblastoma cell line. In both GSCs, signals from myoinositol (Myo-I), UDP-hexosamines (UDP-Hex) and glycine indicated an astrocyte/glioma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 70 publications
4
56
1
Order By: Relevance
“…We next investigated the effect of silencing RYK on two different patient-derived GSC lines (patients #1 and #83) [19]. The ability of GSCs to form neurospheres in vitro was drastically impaired by knocking down RYK expression with a specific siRNA (Figure 2A); moreover, GSC markers were decreased (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the effect of silencing RYK on two different patient-derived GSC lines (patients #1 and #83) [19]. The ability of GSCs to form neurospheres in vitro was drastically impaired by knocking down RYK expression with a specific siRNA (Figure 2A); moreover, GSC markers were decreased (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…GBM tissue specimens were obtained from adult patients undergoing craniotomy at the Institute of Neurosurgery, School of Medicine, Università Cattolica, Rome, Italy, as previously described [19, 26, 27]. Informed consent was obtained from patients before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…1D) in MMC extracts consistent with cellular acetate uptake (26). Importantly, we found evidence of intracellular acetate metabolism through 13 C-labeling of a number of other compounds, mostly in peaks consistent with -CH 2 - in groups at chemical shifts of 2.07 ppm (peak #3, 3-glutamate) (26), 2.35–2.37 ppm (peak #4, 4-glutamate)(26), and 2.53 ppm (glutathione, GSH) (27) (assignments listed in Fig. 1D).…”
Section: Resultsmentioning
confidence: 82%
“…Having found that MMC were sensitive to inhibition of acetate transport using a MCT1 inhibitor (CHC), we next evaluated effects of blocking acetate incorporation into membrane long-chain fatty acids (- 13 CH 2 - and 13 CH 3 ) (precursors to membrane biogenesis (11, 27)), by using the FASN inhibitor orlistat (Fig. 2A and 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an MS-based analysis has shown that the distribution of phosphatidylcholines and phosphatidylethanolamines, components of MLs, is significantly altered between embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), suggesting that differences in lipid metabolism, among others, may be linked to important regulatory differences underlying ESC and iPSC biology (Meissen et al, 2012). Interestingly, there have also been reports that MLs are elevated in glioblastoma cancer stem cells; however, as different groups have published conflicting results, it remains to be seen whether MLs are a marker of sternness or apoptosis (Ramm et al, 2011; Loewenbrück et al, 2011; Guidoni et al, 2014). In addition to lipogenesis, there are important studies outlining changes in energy metabolism between differentiated cells and stem cells (Fig.…”
Section: Steady-state Profilingmentioning
confidence: 99%